Reporting Clinical Significance in Hip Arthroscopy: Where Are We Now?. Issue 2 (December 2020) - Polascik, Breanna A.; Peck, Jeffrey; Cepeda, Nicholas; Lyman, Stephen; Ling, Daphne
Background: Although p values are standard for reporting statistical significance of patient-reported outcome measures (PROMs), the shift toward clinically important outcome values, including minimal clinically important difference (MCID) and substantial clinical benefit (SCB), necessitates re-evaluation of the current literature. Questions/Purposes: We sought to answer two questions regarding studies on primary hip arthroscopy performed for the treatment of femoroacetabular impingement syndrome (FAIS). (1) Do such studies reporting statistical significance on common PROMs meet published MCID/SCB thresholds? (2) What proportion of such studies report both statistical and clinical significance? Methods: We identified four papers published in two journals defining MCID/SCB values on the modified Harris Hip Score (mHHS), Hip Outcome Score–Activities of Daily Living (HOS-ADL), Hip Outcome Score-Sport (HOS-Sport), international Hip Outcome Tool (iHOT-33), and its short version (iHOT-12) for different groups of FAIS patients undergoing hip arthroscopy. We reviewed these two journals from the dates of publication to the present to identify papers reporting changes in post-operative PROMs. The difference in pre- and post-operative scores on each PROM was calculated and compared to MCID/SCB thresholds. Results: Twelve studies were included. Ten studies (83%) evaluated mHHS (90% met MCID, 50% met SCB), seven (58%) evaluated HOS-ADL (100% met MCID/SCB) and HOS-Sport (100% met MCID, 57% met SCB), and one (8%) evaluated iHOT-33 (met MCID/SCB) and iHOT-12 (met MCID). Most studies met MCID and SCB at both 1- and 2-year timepoints. Of the studies evaluated, 50% reported clinical relevance. Conclusions: Nearly all studies evaluated met MCID, while fewer met SCB. Only half discussed these clinical measures. It is proposed that all future studies report both statistical and clinical significance as standard best practice.